PENGARUH DOSIS PUPUK DAN JERAMI PADI TERHADAP KANDUNGAN UNSUR HARA TANAH SERTA PRODUKSI PADI SAWAH PADA SISTEM TANAM SRI (System of Rice Intensification) - Hanafi Ansari; Jamilah Jamilah; Mukhlis Mukhlis (Universitas Sumatera Utara, 2014)
ABSTRACTThis research purposed to know the influence of the straw ricew treatmeant and the NPK fertilizerdosage to the chemical nature growth and the field rice production (Oriza Sativa L) to the soil fieldwith the SRI (System of Rice Intensification) system. This research do in Air Hitam village, LimaPuluh Sub District and analyzed in chemical and fertilizer laboratory Agriculture Faculty,University North Sumatera. This research using the draft of separate plot with the main slot of therice straw treatment on the J0 (The rest of the straw left), J1 (straw cleared and embedded), J2(Leftover straw immersed in tripe + manure) and on the sub plot of F0 (without fertilizer). F1 (doseof fertilizer NPK 50%), F2 (dose of fertilizer NPK 100%). From the research result of the strawtreatment influence to the C-organic, total N, P-available, K-exchanged soil, high of plant, numberof filler in the grain weight but not influence to the pH soil and grain weight. The fertilizertreatment influence to the plant hight and the grain weight but not in influence to the pH, C-organic, total N, K-exchanged soil, grain weigh. While the interaction between the straw treatment and thefertilizer treatment only influence the P available.Key words :SRI, straw of rice, NPK fertilizer